2018
DOI: 10.1038/s41598-018-25135-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated leptin and decreased adiponectin independently predict the post-thrombotic syndrome in obese and non-obese patients

Abstract: Post-thrombotic syndrome (PTS) is a common complication of deep vein thrombosis (DVT). Little is known about the involvement of adipokines in the pathogenesis of DVT. We evaluated whether adipokines can predict PTS. In a prospective cohort study, 320 DVT patients aged 70 years or less were enrolled. Serum adiponectin, leptin and resistin levels were measured three months since the index first-ever DVT. After 2 years’ follow-up PTS was diagnosed in 83 of 309 available patients (26.9%) who had 13.9% lower adipon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…However, RNA sequencing data is often considered to be reliable in itself, since DESeq2 normalization corrects for all gene expression. In respect to the difference in BMI, it is promising that the predictive value of adiponectin was shown to be independent of BMI [7]. Nevertheless, additional research is needed to confirm our findings.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…However, RNA sequencing data is often considered to be reliable in itself, since DESeq2 normalization corrects for all gene expression. In respect to the difference in BMI, it is promising that the predictive value of adiponectin was shown to be independent of BMI [7]. Nevertheless, additional research is needed to confirm our findings.…”
supporting
confidence: 52%
“…In a recent cohort study, low adiponectin levels at three months after DVT were shown to predict the onset of PTS. [7] Finally, there was a decreased expression of the gene PPIA, which codes for cyclophilin A. Besides an intracellular role in protein trafficking, this protein is also secreted by leukocytes in response to inflammatory stimuli.…”
mentioning
confidence: 99%
“…In a prospective cohort study comprising 320 patients with a first DVT, higher leptin levels, independent of obesity, predicted the occurrence of post thrombotic syndrome. 23…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study comprising 320 patients with a first DVT, higher leptin levels, independent of obesity, predicted the occurrence of post thrombotic syndrome. 23 In contrast to the scarce clinical data on the relationship between leptin and VTE risk, several in vitro studies have investigated the effect of leptin on platelet activation parameters 36 and on the expression of key hemostatic factors for blood coagulation and fibrinolysis. [17][18][19]37,38 In human peripheral mononuclear cells, leptin was shown to induce TF activity, antigen and messenger ribonucleic acid (mRNA) expression, 17,18 as well as the release of TF-bearing microparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation